Cognitive and Behavioral Profiles of Children with Aspartylglucosaminuria: A Case Series - Crowe, Louise M.; Brown, Amy; Peters, Heidi (Journal of Pediatric Neurology, 2021)
Aspartylglucosaminuria (AGU) is a rare lysosomal storage disorder with an autosomal recessive inheritance. It affects the aspartylglucosaminidase (AGA) gene and causes a deficiency in activity of the enzyme N-aspartyl-β-glucosaminidase with resultant accumulation of glycoasparagines in body tissues. Children with AGU present with developmental delays in cognitive and language skills. Currently, information on cognition and behavior of children with AGU is limited. This case series presents the neuropsychological and behavioral profiles of three children with AGU assessed at two time points. All the three children had full-scale intelligence quotient (IQ) scores in the intellectual disabled range (<70). IQ had declined since their previous cognitive assessment 1 to 2 years prior. Other cognitive skills were significantly below expected levels. Parents reported several behavioral problems and adaptive difficulties. The findings challenge current beliefs that cognition is impaired but stable in children with declines seen in a short time.
Keywords: aspartylglucosaminuria; lysosomal storage disorder; cognition; children; behavior